Radiological Risk Assessment of Adult Exposure to Radionuclides from the New Calabar River, Nigeria - Igbudu, Onukwurumege; Ogan, Abiye Caleb (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2025)
A natural radioactivity study was carried out to determine the annual effective dose (AED) of radiation in adults (12-17 yr and ˃ 17 yr) due to intake of radioelements in river water from some randomly selected points along the stretch of the New Calabar River, Rivers State, Nigeria. Twenty-eight river water samples. collected into a 50 cl sterile sample container were analyzed in Environmental Laboratory, National Institute of Radiation Protection and Research (NIRPR), Nigerian Nuclear Regulatory Authority (NNRA), University of Ibadan, Nigeria, with the aid of NaI gamma ray detector. The detector helped to determine the activity concentration of the radionuclides (40K, 232Th and 232U) in the water. The AED in adults were evaluated from the results of activity concentration as well as appropriate ingested dose conversion factor. Results showed that the mean AED of 40K in adult (12-17 yr and ˃17 yr) as a result of consuming the river water are 0.346±0.018 and 0.282±0.015 mSv y–1 respectively. The mean AED of 232Th in adult (12-17 yr and ˃17 yr) are 0.763±0.044 and 0.702±0.039 mSv y–1 respectively while the mean AED of 232U in the river water are: 4.270±0.557 mSv y–1 for adult (12-17) yr and 2.252±0.252 mSvy–1 for (˃17) yr. Results further indicated that the mean total annual effective dose (TAED) of radiation in adult (12-17 yr and ˃17 yr) as a result of intake of (40K, 232Th and 232U) in river water are 5.347±0.619 and 3.207±0.334 mSvy–1 respectively. This mean TAED was observed to be above the internationally recommended safe limit of 0.10 mSvy–1 for adult 12-17 yr and ˃17 yr). The study can be concluded that the water supplies from the study area are radiologically polluted and harmful for consumption by inhabitants of the study area. Provision of clean, safe, and alternative water supplies by relevant agencies of government, Non-Governmental Organizations are highly recommended for the inhabitants. Further radiological research studies on other areas of the New Calabar River not captured in this study are also recommended to be carried out.